2012
DOI: 10.1523/jneurosci.1461-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Circuit Feedback Specifies Motor Circuit Output

Abstract: Bidirectional communication (i.e. feedforward and feedback pathways) between functional levels is common in neural systems, but in most systems little is known regarding the function and modifiability of the feedback pathway. We are exploring this issue in the crab (Cancer borealis) stomatogastric nervous system by examining bidirectional communication between projection neurons and their target central pattern generator (CPG) circuit neurons. Specifically, we addressed the question of whether the peptidergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 90 publications
0
42
0
Order By: Relevance
“…We would like to emphasize that the choice of the feeding circuit for the study of circuit function of DAACPs is not random, because the expression of specific feeding behavior, which is a motivated behavior, is modulated by many intrinsic and extrinsic factors (36,76) that are often mediated by actions of neuromodulators (36,(77)(78)(79). Consistent with this complexity, previous work has shown that the feeding circuit is extensively modulated by neuromodulators, including neuropeptides that have been discovered in Aplysia (41,42,48,49,66,67,69).…”
Section: Approaches For Identifying Daacps In Biological Tissuementioning
confidence: 99%
“…We would like to emphasize that the choice of the feeding circuit for the study of circuit function of DAACPs is not random, because the expression of specific feeding behavior, which is a motivated behavior, is modulated by many intrinsic and extrinsic factors (36,76) that are often mediated by actions of neuromodulators (36,(77)(78)(79). Consistent with this complexity, previous work has shown that the feeding circuit is extensively modulated by neuromodulators, including neuropeptides that have been discovered in Aplysia (41,42,48,49,66,67,69).…”
Section: Approaches For Identifying Daacps In Biological Tissuementioning
confidence: 99%
“…The influence of projection pathways on neural networks is typically studied assuming a feed-forward architecture, in which descending projection neuron pathways initiate, terminate, or modify the activity of the target network [7, 21, 38, 15]. However, neural circuitry in biological systems is more complex, in that projection neurons receive feedback from their target networks [8, 37, 34, 44]. In rhythmically active oscillatory networks, such feedback can influence the pattern of descending inputs from projection neurons, and, in some cases, rhythmically patterned projection neuron input influences the motor pattern of the target network [41].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting aspect of the type 3 gastric mill rhythms was that short breaks were often visible within individual LG bursts. This is reminiscent of the POC-activated gastric mill rhythms observed in vitro (Blitz and Nusbaum, 2012).…”
Section: Multiple Gastric Mill Rhythms Exist In Vivomentioning
confidence: 63%
“…While the gastric mill rhythm is not always active in vitro (45% active; Stein et al, 2005), it is almost always active in vivo (82% active). Sensory pathways have been shown to activate the gastric mill rhythm (via the actions of descending modulatory projection neurons) both in vitro and in vivo (Blitz and Nusbaum, 2012;Blitz et al, 2004;Saideman et al, 2007;Hedrich et al, 2009Hedrich et al, , 2011Diehl et al, 2013). It is reasonable to assume that the increased amount of gastric mill activity in vivo is due to additionally activated sensory pathways, as most of them are inactive in vitro.…”
Section: Multiple Gastric Mill Rhythms Exist In Vivomentioning
confidence: 99%